Exploring catecholase activity in dinuclear Mn(ii) and Cu(ii) complexes: an experimental and theoretical approach. (5th May 2020) - Ahmad, M. Shahwaz; Khalid, Mohd; Khan, M. Shahnawaz; Shahid, M.; Ahmad, Musheer; Monika,; Ansari, Azaj; Ashafaq, Mo
Abstract : Two dinuclear Mn(ii ) and Cu(ii ) complexes were prepared, characterised and assessed for non-covalent interactions and catecholase oxidase properties. The catecholase activity of 2 is further corroborated by theoretical calculations using DFT. Abstract : While a plenty of work has been done on metal complexes incorporating N- and O-functionalised dicarboxylic acids (iminodiacetic acid and oxydiacetic acid, respectively), S-functionalised dicarboxylic acid, i.e. thiodiglycolic acid (H2 tdga), is less explored and requires attention. In this study, two dinuclear complexes, namely [Mn2 (tdga)2 (phen)2 ]·2CH3 OH (1 ) and [Cu2 (tdga)2 (phen)2 ]·H2 tdga (2 ), were characterised employing spectral, single-crystal X-ray diffraction and DFT/TD-DFT studies. Time-dependent density functional theory (TD-DFT) reveals the types of electronic transition between metal-to-ligand charge transfer (MLCT) and intra-ligand charge transfer (ILCT). The crystal structure reveals the presence of various non-covalent interactions, which are further corroborated from Hirshfeld surface analysis. In EPR spectral analysis, 1 shows an isotropic signal at g = 1.99 due to Mn 2+ (d 5 ) with ground-state term 6 S having a six-coordinate distorted octahedral geometry, while 2 shows two resonances, namely, g ‖ = 2.21 and g ⊥ = 2.11 due to the Jahn–Teller distortion of Cu 2+ (d 9 ) ions. The anisotropic g values are in the order of g ‖ > g ⊥ > 2.0, which is characteristic of an axially elongated tetragonal distortion with a d x 2 – y 2 ground-state energy level. Assessment of catecholase-like activity provides K cat = 962.56 (h −1 ) for 2, indicating enhanced enzymatic activity of 2 towards the oxidation of catechol (3, 5-DTBC) to a quinone derivative (3, 5-DTBQ). The catecholase activity of 2 is also corroborated by density functional theory (DFT) analysis.